A comprehensive review of virgin coconut oil: Extraction methods and diverse applications - Thimmana, G B; Kumar, M; Geethanjali, S; Vani, V; Suresh, J (Plant Science Today, 2025)
The extraction of virgin coconut oil (VCO) is a critical process that yields premium oil from fresh coconut meat. Renowned for its numerous health benefits and wide-ranging applications in the food, cosmetics, and pharmaceutical industries, VCO has attracted a lot of interest. Traditional cold pressing methods coexist with modern techniques such as centrifugation and enzyme-assisted extraction. Each method has its own benefits and drawbacks that influence the quality of the end product. To optimize VCO production and maintain its superior quality, it is crucial to understand the extraction procedure, including key factors like acidity, colour, scent, moisture content, and fatty acid composition. Rich in medium-chain fatty acids (MCFAs), particularly lauric acid, VCO exhibits potent antibacterial and antioxidant properties, offering significant health and wellness benefits. VCO has diverse industrial applications. It serves as an active ingredient in pharmaceutical formulations, a base oil in cosmetics, a cooking oil, and a component in various food products. It unique combination of nutritional and functional qualities makes it an ideal choice for manufacturers seeking natural and sustainable ingredients. This review focuses on the production methods, physiochemical properties, health benefits, and industrial applications of VCO extraction.